The psychology of female sport performance from a gender perspective - Roberts, C.-M.; Quesnel, D. A. (The active female. Health issues throughout the lifespan, 2023)
Gender, the non-physiological aspects of being male and female, is engrained in the expectations that society holds for us. It helps us understand how and why behavior and experiences in sport may vary. As a female athlete, the psychology of sport is heavily influenced by socially driven gender expectations. It is important that these gender perspectives are understood because their influences can ultimately impact sport performance. In the case of a female athlete, the influence of gender in sport is more often negative than positive. This chapter examines the nuances of the psychology of the female athlete from a gender perspective. It covers the gender differences often observed in the levels of self-confidence and the management of competitive state anxiety. The chapter goes on to discusses the research underpinning the gender differences in motivation to engage in and excel in sport and the distinctiveness of the cohesion-performance relationship in all-female teams. An assessment is made of sport-related stressors specific to the female athlete and common approaches to coping, including the increasingly important role of self-compassion. In addition, the high-risk status of female athletes in regard to weight pressures, body dissatisfaction, and disordered eating is addressed, including the influential role of the coach in this equation. Coaching, coach behaviors, and the coach-female athlete relationship are examined alongside the deleterious role of microaggressions that single out gender as the identifying characteristic of the female athlete—not her strength, dedication, or performance. Overall, this chapter will provide the background necessary to understand the psychology of female sport performance, from a gender perspective.